More accounting changes : financial reporting through the age of crisis and globalization - Herz, Robert H., 1953- (Emerald, 2016)
This volume, More Accounting Changes, is a revised and updated edition of Herz's earlier work (Accounting Changes), reflecting: developments in financial reporting; global developments regarding the use of International Financial Reporting Standards; current efforts at disclosure modernization and simplification by the SEC and FASB; and more developments in the field
Keywords: 20.-21. století; účetnictví; účetní standardy; účetní výkazy; dějiny účetnictví -- 20.-21. století; accounting; accounting standards; financial statements; history of accounting -- 20th-21st centuries; populárně-naučné publikace; popular works